Ulvan based materials doped with lithium sulfate salts as solid biopolymer electrolytes for energy storage applications - (:unkn) unknown (Elsevier BV, 2024)
The conversion of algae biomass into high-value technological materials can promote the utilization of green algae and mitigate issues such as green tides and biofouling. This paper reports, for the first time, the utilization of ulvan in the production ...
Keywords: Biopolímeros; Almacenamiento de energía